THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) AND LEARNING ANALYTICS IN PHYSICS EDUCATION - Vazira Isomiddinovna Ibragimova (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article examines the theoretical foundations and pedagogical potential of Artificial Intelligence (AI) and Learning Analytics in physics education. It explores how intelligent tutoring systems, adaptive learning algorithms, and data-driven decision-making tools can enhance conceptual understanding, experimental reasoning, and individualized instruction in physics classrooms. The research highlights the integration of AI-based analytics with constructivist pedagogy, emphasizing their role in supporting personalized learning, real-time feedback, and data-informed teaching strategies.